UJI BEBERAPA FORMULASI PUPUK HAYATI BERBAHAN AKTIF BAKTERI Bacillus. sp ENDOFIT PADA TANAMAN TOMAT (Lycopercisum esculentum Mill.) - Marpaung, Win Nicho; Puspita, Fifi; Ali, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to observe the effect of some formulation of bio-fertilizer containing Bacillus sp. endophytes and to obtain the best formulation to increase the growth and production of tomatoes plant. The research has been conducted at the experimental farm, Faculty of Agriculture, University of Riau in March to August 2016. The research was arranged in a completely randomized design (CRD) and consisted of 5 treatments : Bs0 (Bacillus sp. without formulation), BsAk (Bacillus sp.+Coconut Water+Rice hulle Ash 1%+10% molasses), BsLs (Bacillus sp.+Palm Oil Mill Effluent+Rice hulle Ash 1%+10% molasses), BsLt (Bacillus sp.+Tofu Mill Effluent+Rice hulle Ash 1%+10% molasses) BsUs (Bacillus sp.+Cow Urine+Rice hulle Ash 1%+10% molasses). Data were analyzed statistically by analysis of variance and continued with DNMRT at 5% confident level. The result of the research showed that the formulation of Bacillus sp. was significantly affected on the plant height, fruit weight per fruit and fresh cenopy plant weight, but not significantly effected on stem diameter, flowering age, harvesting age, the amount of fruits, fruits diameter, fruits weight per plant and roots volume. Formulation of Bacillus sp. with coconut water is the best formulation in increasing the growth of tomatoes plant while the formulation of Bacillus sp. with cow urine is the best formulation in increasing the production of tomatoes plant.Keywords: Biofertilizer, Bacillus sp., tomatoes, liquid waste.